Research and development of guided-wave optical components for WDM network technology - Chan, Yuen Chuen (2008)
In this project, optoelectronic device fabrication and integration as well as sol-gel erbium doped sol-gel processing and optical waveguides have been studied for applications specific to the WDM technology.